STUDENTS’ PERCEPTION OF CAKE APPLICATION FOR STUDENTS’ SPEAKING SKILLS - Audrin Bianca Mareta; Yuyun Hendrety; Rahma Dianti (Didascein : Journal of English Education, 2025)
A great use of information and communication technology (ICT) has recently affected language pedagogy. ICT usage shifts how English is taught and learned. Many people nowadays use mobile apps as a solution for language learning. One of the smartphone applications that students have been using lately is the Cake application. This study investigates students' perceptions and benefits of using the Cake application in English learning at Sandika Sukajadi High School, Banyuasin. A quantitative method featuring a survey design was employed as the research framework. 104 students, who were selected using a total sampling technique, participated as the sample in this study. A closed-ended questionnaire, distributed using Google Forms, was used to collect the data, which was then analyzed using percentage analysis. The findings revealed that most students perceived positively of using the Cake app for learning spoken English. This study found that (1) the Cake app is a helpful, user-friendly, and interesting tool for students in the English learning process, and (2) the Cake app has many benefits for students in improving their English speaking skills. With its flexibility, it enables students to manage their self-paced learning. Students can have a greater chance to improve their speaking skills using the Cake application.